Introduction - Exploring the Kurdish Movement: Power Relations, Historical Dynamics and Theoretical Perspectives - Grasso, Davide; Novellis, Andrea (PARTECIPAZIONE E CONFLITTO, 2025)
This editorial positions Kurdish politics at a turning point initiated by the PKK’s 2025 decision to dissolve its armed wing and by concomitant institutional realignments in Turkey, Syria, Iraq, and Iran. Building on feminist, post-colonial, and transnational scholarship, the special issue advances a three-level framework. First, it traces the historically sedimented repertoires of state coercion and colonial governance that define Kurdish political opportunities. Second, it examines the movement’s evolving ideological corpus-especially Democratic Modernity and Jineolojî-which articulates a counter-theory of decentralised authority. Third, it analyses the micro-processes of recruitment, activist identity formation, and disciplined internal hierarchy that embed revolutionary ideas in everyday practice. A state-power cluster, an ideology cluster, and a micro-sociology study show the framework’s reach. Two cross-cutting themes structure the issue: power, understood as the intersection of coercive sovereignty, revolutionary decentralisation, and intra-movement organisation; and history, viewed simultaneously as a state instrument of closure and a movement resource for alternative futures. Building on the volume’s findings, the introduction sketches three forward research paths: (i) a sociology of mobilisation under post-insurgency transition; (ii) a comparative politics agenda on peace settlements, DDR, and autonomy design; and (iii) a political-theory programme probing how post-statist and decolonial imaginaries can be institutionalised.